DAMPAK PERNIKAHAN DINI DALAM KELUARGA DI NAGARI TALANG BABUNGO - Siti Lutfiyah; Suryadi; Fuaddillah Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early marriage is a social phenomenon that is prone to causing family role dysfunction due to the couple’s lack of readiness in various aspects of their development. This study aims to describe the impact of early marriage on families in Nagari Talang Babungo. This study employs a quantitative approach using a descriptive method. The population for this study comprised all couples who had entered into early marriages in Nagari Talang Babungo, with a sample size of 30 individuals (15 couples) selected using total sampling. Data were collected using a questionnaire based on a Likert scale comprising 33 statements, which had been validated through expert judgement. Data analysis was conducted using descriptive percentage analysis with the aid of Microsoft Excel. The results of this study revealed that the impact of early marriage on families falls into the high category (50 per cent). This finding implies the importance of strengthening pre-marital counselling programmes, both by formal educational institutions and the Office of Religious Affairs (KUA), in order to educate young people about their readiness before entering into marriage. This study recommends that the community and young people should not be easily influenced into entering into early marriage, and should be more aware of the consequences of early marriage.